Gambaran Karakteristik Epilepsi Pada Pasien Anak Di Ruang Rawat Inap Rsud Arifin Achmad Provinsi Riau - Sari, Siska Permata; Ismet, Ismet (Fakultas Kedokteran Universitas Riau, 2024)
Epilepsy is one of the most common causes of morbidity in pediatric neurology, causing learning difficulties, impaired growth and development, and impaired quality of life. Epilepsy has three categories of seizures, namely focal seizures, generalized seizures and seizures that cannot be classified. This study aims to determine the Characteristics of Epilepsy in Pediatric Patients in the Inpatient Room of Arifin Achmad Hospital, Riau Province, 2018-2021 Period. There were 64 cases of epilepsy in children, the most age 0-5 years (56,3%), in males (60,9%), did not have a family history of epilepsy (89,1%), with the most seizure type generalized seizure (54,7%), the drug given was valproic acid (17,2%), a combination of luminal with valproic acid as much as (20,3%) and 17,2% suffered from cerebral palsy. From the results of this study, it can be concluded that most epilepsy patients aged 0-5 years are predominantly male with no family history of epilepsy. The type of seizure is generalized seizures with the most management of valproic acid and diagnosed with cerebral palsy.